Professional Development in Crisis: Toward Resilient Society. Issue 1 (14th October 2022) - Rorissa, Abebe; Mawire, Blessing; Shah, Chirag; Sonnenwald, Diane; Khazaree, Emad; Imeri, Aylin; Hilal, Imane
Abstract: Professional development is one of the pillars of personal and professional success because it is the catalyst for professional fulfillment and a way to improve one's skills and excel professionally. However, this subject is not addressed enough in academic courses, therefore students and new recruits start learning while being challenged without strong enough prerequisites to support them. The objective of the panel is to gather ideas from different scholars and professionals; to exchange ideas and experiences around the different themes of this subject to empower students and professionals in their early career stages and make them more resilient in a hyper‐competitive society and uncertain world.